Intensitas Mendengarkan Musik K-Pop dengan Self-Love dan Kesehatan Mental Mahasiswa - Andi Desviana Indasari; Dhevy Puswiartika; Dian Fitriani (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2025)
This research investigates the relationship between listening K-Pop music consumption and levels of Self-Love and mental health among students in the Faculty of Teacher Training and Education, class of 2021, at Tadulako University. The research participants consisted of 146 students from the Faculty of Teacher Training and Education, a 2021 batch, who actively listened to K-Pop music. Data collection employed adapted questionnaire instruments: a listening K-Pop music consumption questionnaire, a Self-Love scale, and a mental health assessment scale. The research employed a quantitative research methodology with a causal-associative design, utilizing correlation analysis to examine the relationships between variables. The Pearson Product-Moment correlation analysis yielded the following results: The correlation between BTS music consumption (Variable X) and Self-Love (Variable Y1) had a significance value (2-tailed) of 0.483, which is greater than 0.05. Similarly, the correlation between listening K-Pop music consumption (Variable X) and mental health (Variable Y2) yielded a significance value (2-tailed) of 0.877, which is greater than 0.05. Based on these statistical findings, both relationships demonstrate non-significant correlations. For the BTS music and Self-Love variables, the significance value (2-tailed) exceeds 0.05, leading to the rejection of the alternative hypothesis (Ha). which means there is no relationship between listening K-Pop music and Self-Love and mental health____________________________________________________________ Penelitian ini bertujuan untuk mengetahui hubungan antara intensitas mendengarkan musik K-Pop dengan Self-Love dan kesehatan mental mahasiswa Fakultas Keguruan dan Ilmu Pendidikan angkatan 2021, subjek dalam penelitian ini adalah mahasiswa Fakultas Keguruan dan Ilmu Pendidikan angkatan 2021 Universitas Tadulako yang mendengarkan intensitas mendengarkan musik K-Pop. Jumlah subjek pada penelitian ini sebanyak 146 mahasiswa. Pengumpulan data dilakukan dengan menggunakan kuesioner adaptasi yaitu kuesioner intensitas mendengarkan musik K-Pop, skala Self-Love, dan skala kesehatan mental. Metode penelitian yang digunakan adalah kuantitatif dengan jenis penelitian asosiatif kausal menggunakan analisis korelasi. Hasil dari uji korelasi Product Moment Pearson terhadap variabel X dengan variabel Y1 diketahui nilai variabel intensitas mendengarkan musik K-Pop dengan variabel Self-Love signifikan (2-tailed) 0,483 > 0,05. Pada variabel X dengan variabel Y2 diketahui nilai variabel intensitas mendengarkan musik K-Pop dengan variabel kesehatan mental signifikan (2-tailed) 0,877 > 0,05. Maka Hipotesis alternatif (Ha) ditolak yang artinya tidak ada hubungan intensitas mendengarkan musik K-Pop dengan Self-Love. Pada variabel intensitas mendengarkan musik K-Pop dengan kesehatan mental hasil analisis menunjukkan bahwa nilai signifikan (2-tailed) > 0,05 maka Hipotesis alternatif (Ha) ditolak yang artinya tidak ada hubungan intensitas mendengarkan musik K-Pop dengan Self-Love dan kesehatan mental.